2002
DOI: 10.1177/147323000203000402
|View full text |Cite
|
Sign up to set email alerts
|

A New Fixed-Dose Combination for Added Blood Pressure Control: Telmisartan Plus Hydrochlorothiazide

Abstract: Population surveys on hypertension management reveal worrying deficiencies in the awareness and treatment of high blood pressure. Many patients with hypertension will require two or more drugs with complementary mechanisms of action (which generally have additive effects, producing greater blood pressure reductions than either agent alone) to attain the blood pressure goals specified in internationally accepted guidelines. Nevertheless, physicians are often reluctant to prescribe multiple anti-hypertensive dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…In this study, telmisartan in fixed‐dose combination with HCTZ was well tolerated, with adverse event rates being low. In accordance with previous reports, 19–23 the addition of a 12.5 mg dose of HCTZ to telmisartan did not have a negative impact on its tolerability profile. The addition of telmisartan to HCTZ also attenuates the potassium loss that is commonly associated with high‐dose HCTZ therapy 19 .…”
Section: Discussionsupporting
confidence: 92%
“…In this study, telmisartan in fixed‐dose combination with HCTZ was well tolerated, with adverse event rates being low. In accordance with previous reports, 19–23 the addition of a 12.5 mg dose of HCTZ to telmisartan did not have a negative impact on its tolerability profile. The addition of telmisartan to HCTZ also attenuates the potassium loss that is commonly associated with high‐dose HCTZ therapy 19 .…”
Section: Discussionsupporting
confidence: 92%
“…Many authors have demonstrated the superiority of telmisartan when combined with other antihypertensives like amlodipine or HCT compared to monotherapy. [11][12][13][14]. Telmisartan combinations were also better in BP reduction compared to other ARB combinations [15].…”
Section: Open Accessmentioning
confidence: 77%
“…Our analysis suggest as many have before us [33,[47][48][49][50][51][52]] that the combination of ARB and a thiazide diuretic is more effective for the control of systolic and diastolic blood pressure than the use of the ARB or diuretic alone. When it comes to a comparison between the combinations ARB/HCTZ and ARB/CTLD pooled results show a WMD of −6.30 mmHg (−7.30, −5.29) in favor of the combination containing CTLD for control of systolic blood pressure.…”
Section: Discussionmentioning
confidence: 69%